What happens when natalizumab therapy is stopped?. (September 2011) - Schaaf, Stephen M; Pitt, David; Racke, Michael K
Evaluation of: O''Connor PW, Goodman A, Kappos L et al. Disease activity return during natalizumab treatment interruption in patients with multiple sclerosis. Neurology 76(22), 1858–1865 (2011). Natalizumab is an α-4 integrin antagonist used for the treatment of relapsing multiple sclerosis (MS). Concerns with the drug have a risen owing to a heightened risk of progressive multifocal leukoencephalopathy, which has caused some physicians to interrupt or stop treatment altogether. The article under review evaluates the safety of natalizumab treatment interruption, including the rate and magnitude of the return of MS disease activity toward baseline levels by clinical and MRI measures. The investigators found that by 4–7 months after natalizumab treatment interruption, MS disease activity began to reach baseline levels, which is consistent with the known elimination kinetics of natalizumab. The duration of prior natalizumab exposure or alternate MS treatments during interruption was demonstrated to not affect return of disease activity. Despite nearly similar disease activity after natalizumab treatment, patients with highly active disease prior to treatment had a return of disease activity that was greater in magnitude when compared with those with less active disease. Most significantly, the study did not show evidence of rebound following natalizumab cessation. We agree with these conclusions, but note that a subgroup of MS patients may demonstrate highly active disease after natalizumab cessation.